2023
DOI: 10.1186/s12964-022-01033-9
|View full text |Cite
|
Sign up to set email alerts
|

FKBP12 is a major regulator of ALK2 activity in multiple myeloma cells

Abstract: Background The immunophilin FKBP12 binds to TGF-β family type I receptors, including the BMP type I receptor ALK2. FKBP12 keeps the type I receptor in an inactive state and controls signaling activity. Removal of FKBP12 with drugs such as the FKBP-ligand FK506 enhances BMP activity in various cell types. In multiple myeloma cells, activation of SMAD1/5/8 leads to apoptosis. We hypothesized that removing FKBP12 from ALK2 in myeloma cells would potentiate BMP-induced ALK2-SMAD1/5/8 activity and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…In multiple myeloma, BMP4 inhibits tumor growth and induces apoptosis by suppressing c-MYC via a SMAD-dependent pathway . Furthermore, treatment with the immunosuppressive drug FK506 enables BMP4 signaling through ALK2 and ALK3, leading to tumor-suppressive effects via SMAD1/5/9 activation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiple myeloma, BMP4 inhibits tumor growth and induces apoptosis by suppressing c-MYC via a SMAD-dependent pathway . Furthermore, treatment with the immunosuppressive drug FK506 enables BMP4 signaling through ALK2 and ALK3, leading to tumor-suppressive effects via SMAD1/5/9 activation …”
Section: Discussionmentioning
confidence: 99%
“…38 Furthermore, treatment with the immunosuppressive drug FK506 enables BMP4 signaling through ALK2 and ALK3, leading to tumor-suppressive effects via SMAD1/5/9 activation. 39 Similarly, BMP4 expression is reduced in CD tumor tissues compared to that in normal human pituitary tissues. 8 In this study, we not only verified the low expression of BMP4 in corticotroph PitNETs but also found that the downstream p-SMAD1/5/9 also showed low expression levels in the nucleus.…”
Section: Acs Pharmacologymentioning
confidence: 99%
“…INA-6 ALK2 knockout (k.o.) cells and negative control cells were generated using CRISPR/Cas9 technology as recently described 50 .…”
Section: Methodsmentioning
confidence: 99%